Actual and potential distribution of Dendroctonus mexicanus Hopkins under two climate change scenarios - Méndez Encina, Fátima Monserrat; Méndez González, Jorge; Cerano Paredes, Julián (Instituto de Ecología, A.C., 2020)
Climate exerts a dominant control over the natural distribution of species. Bioclimatic models are an important tool for assessing the potential responses of species to climate change. The objective of this study was to estimate the distribution of Dendroctonus mexicanus Hopkins, under current and future climate scenarios (year 2050) in two Representative Concentration Pathway (RCP´s) 4.5 and 8.5. Characteristics of model (creation, calibration, selection and evaluation) were carried out in kuenm, an R package that uses Maxent as the modeling algorithm. Model suitability of D. mexicanus was composed mainly by mean temperature of warmest quarter (76.6%), temperature annual range (12.5%) and precipitation of driest quarter (5.5%). In Mexico, the high suitability of D. mexicanus is 121 310.7 km2; only five states: State of Mexico (17 879.7), Michoacan (15 669.8), Puebla (14 693.1), Oaxaca (14 380.1) and Hidalgo (13 830 km2), comprise more than 63% of the estimated high suitability. For 2050 it is estimated a decrease of 51 thousand km2 of climatic suitability specially in Michoacan, Jalisco and Guanajuato, but an increase of about 25 thousand km2 toward northwest Mexico. A shift and a probable migration of this bark beetle toward higher latitudes (30 ± 15 km) and altitudes (~ 100 m) extending its distribution up to 3700 masl is feasible. These relevant changes in their probably distribution may involve potential forest damage.